2019
DOI: 10.1093/pm/pnz070
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalgesia and Central Sensitization Signs in Patients with Cluster Headache: A Cross-Sectional Study

Abstract: Objective To investigate central sensitization (CS) in cluster headache (CH) and to evaluate its relationship with disease characteristics and psychological comorbidities. Design Cross-sectional study. Settings Whether CS occurs in CH, as it does in other primary headaches, is a subject of debate. Few studies have evaluated the presence of CS and its relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
4
16
1
Order By: Relevance
“…Recent reviews have reported that PPTs are consistently lower in patients with migraine or tension‐type headache when compared with asymptomatic healthy subjects, with the trigemino‐cervical region being the most sensitive area . Our findings supporting the presence of widespread pain hyperalgesia and central sensitization in individuals with CH agree with those of Ladda et al, Fernández‐de‐las‐Peñas et al, and Gil‐Martínez et al However, these studies included small samples (ranging from 16 to 20) and did not control for the presence of depressive and anxiety levels, which could modify the excitability of central pain pathways . In fact, our study is the first one investigating widespread pressure pain hyperalgesia in individuals with CH that controlled for the potential effects of depression and anxiety, and is also the one with the largest sample to date.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Recent reviews have reported that PPTs are consistently lower in patients with migraine or tension‐type headache when compared with asymptomatic healthy subjects, with the trigemino‐cervical region being the most sensitive area . Our findings supporting the presence of widespread pain hyperalgesia and central sensitization in individuals with CH agree with those of Ladda et al, Fernández‐de‐las‐Peñas et al, and Gil‐Martínez et al However, these studies included small samples (ranging from 16 to 20) and did not control for the presence of depressive and anxiety levels, which could modify the excitability of central pain pathways . In fact, our study is the first one investigating widespread pressure pain hyperalgesia in individuals with CH that controlled for the potential effects of depression and anxiety, and is also the one with the largest sample to date.…”
Section: Discussionsupporting
confidence: 88%
“…Fernández‐de‐las‐Peñas et al also observed pressure pain hypersensitivity in both symptomatic and distant pain‐free areas in 16 men with episodic CH during a remission phase compared to controls. More recently, Gil‐Martínez et al found hypersensitivity to pressure pain at cranial and extra‐cranial points in 20 patients with episodic or chronic CH. The results of these studies all support the presence of widespread pressure pain hyperalgesia in CH.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence showing the presence of pressure pain hypersensitivity over the trigeminal area in patients with CH. Yet, some authors have reported bilateral hypersensitivity to pressure pain [4,5], whereas others have described an asymmetry whereby the symptomatic side was more sensitive than the non-symptomatic side [6]. In all these studies, measurements were conducted on specific points in each of the head regions studied [4,5,6].…”
Section: Introductionmentioning
confidence: 99%